Self Control Improvement to Reduce The Addiction of Using Smartphone with Content Powering Services in The Students of SMAN 1 Sungai Limau - Alen Okta Iranda; Neviyarni Neviyarni (Jurnal Neo Konseling, 2020)
Self control smartphone usage is the ability of a person to arrange, guide, organize and direct their thoughts, behavior and decisions in doing something by considering the needs and consequences that will result. This study aims to reduce addiction to smartphone usage from higher to lower levels by students of SMAN 1 Sungai Limau by increasing self control using content mastery services. This research uses quantitative methods with the type of BK service action research. The research subjects were 24 students of Sungai Limau SMAN 1 class X IPS-1. The data collection tool used is the instrument scale. The data analysis technique was using Wilcoxon signed range test design data analysis.The results showed that content mastery services can improve self control in reducing smartphone addiction in students with 60% pretest results in the medium and posttest categories increasing to 76.02% in the high category. This study gives meaning that content mastery services have succeeded in increasing self control to reduce smartphone addiction for students.